2016
DOI: 10.1167/iovs.16-20103
|View full text |Cite
|
Sign up to set email alerts
|

Glycyrrhizin Reduces HMGB1 and Bacterial Load in Pseudomonas aeruginosa Keratitis

Abstract: PurposeHigh mobility group box 1 (HMGB1) contributes to poor disease outcome in Pseudomonas aeruginosa keratitis. This study tests the prophylactic effect of treatment with HMGB1 inhibitors, glycyrrhizin (GLY) and its derivative, carbenoxolone (CBX), for Pseudomonas keratitis.MethodsWe treated C57BL/6 (B6) mice subconjunctivally with GLY or CBX, infected with a noncytotoxic clinical isolate (KEI 1025) or a cytotoxic strain (ATCC 19660) of P. aeruginosa, and injected intraperitoneally with either agent. Clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
63
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(76 citation statements)
references
References 57 publications
8
63
0
Order By: Relevance
“…The effects of GLY have been investigated in a wide range of diseases, such as rat myocardial ischemia/reperfusion-induced injury, intracerebral hemorrhage, and Pseudomonas aeruginosa keratitis. The indicated studies confirmed that GLY is a potent HMGB1 inhibitor [38-40]. Consistent with the results of these studies, in this study, we showed that GLY had inhibitory effects on HMGB1 expression and release.…”
Section: Discussionsupporting
confidence: 92%
“…The effects of GLY have been investigated in a wide range of diseases, such as rat myocardial ischemia/reperfusion-induced injury, intracerebral hemorrhage, and Pseudomonas aeruginosa keratitis. The indicated studies confirmed that GLY is a potent HMGB1 inhibitor [38-40]. Consistent with the results of these studies, in this study, we showed that GLY had inhibitory effects on HMGB1 expression and release.…”
Section: Discussionsupporting
confidence: 92%
“…This trend in antibiotic resistant bacterial infections is of serious global concern, fueled by the lack of effective antibiotics available and few being developed. 3 GLY, derived from Glycyrrhiza glabra, is antimicrobial and anti-inflammatory 6 ; it has many additional effects 6 and has shown promise against non-MDR isolates 7,8,16,19,20 and our current work shows it is effective against MDR isolates. Clinically, GLY also has been successfully used to treat blepharitis 28 and hepatitis patients 29,30 with no toxicity.…”
Section: Discussionmentioning
confidence: 60%
“…In past work, we never observed different GLY MICs when testing several non-MDR clinical isolates. 7,19,20 We also tested the MIC of ciprofloxacin, to which MDR9 is resistant and found an MIC of 32 lg/mL. The MIC for GLY together with ciprofloxacin showed that GLY reduced ciprofloxacin MIC 2fold, suggesting that less antibiotic could be used for treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concomitant, heavy cellular infiltrates are identified in the anterior chamber, which is also called the hypopyon. Typically, in the later stages corneal ulcers occur (18). Corneal ulcers are estimated to cause approximately two million new cases of monocular blindness every year (1).…”
Section: Introductionmentioning
confidence: 99%